FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUTUSAN PELANGGAN DALAM MEMILIH KEMBALI JASA PELAYANAN RAWAT INAP DI RUMAH SAKIT ISLAM JOMBANG - Muhammad Zulfikar; Abdul Ghofar (Eduhealth, 2010)
AbstractCustomer behavior in decision-making of choosing a facility inpatient services is influenced by several factors include social, cultural, individual and psychological. With customer expectations get a sense of security in fulfilling the need in solving health problems, so the hospital must improve services and give satisfaction commensurate with the costs incurred by the patient.This type of analytic study correlation with Cross Sectional design. Independent variables in this study are factors associated with the customer's decision of social, cultural, individual, psychological. While the dependent variable is the decision in selecting back rawayat inpatient services. This research instruments used Questioner then tabulated and analyzed using Spearman's Rho test statistic with a value of α = 0.05.The results of Spearman's Rho test statistic value of 0.007 obtained from the individual factors, psychological factors 0.001, 0.011 from social factors, cultural factors 0.023 from the value of α = 0.05, where H 0 is rejected and H 1 accepted which means there is a relationship between factors associated with the customer's decision in selecting back-patient services at the Islamic Hospital Jombang.Decision customers choose inpatient services is influenced by several factors including: individual factors, psychological factors, social factors and cultural factors. Thus, the client has authority to make a decision in the use of hospital services both in the service of safe, comfortable and can meet clients' needs and expectations. Keywords: individual factors, psychological factors, social factors, cultural factors, the customer's decision.